Marginal Zone B Cells Induce Alloantibody Formation Following RBC Transfusion - Patel, Seema R.; Gibb, David R.; Girard-Pierce, Kathryn; Zhou, Xiaoxi; Rodrigues, Lilian Cataldi; Arthur, Connie M.; Bennett, Ashley L.; Jajosky, Ryan P.; Fuller, Megan; Maier, Cheryl L.; Zerra, Patricia E.; Chonat, Satheesh; et al. (Frontiers in Immunology, 2018)
Red blood cell (RBC) alloimmunization represents a significant immunological challenge for some patients. While a variety of immune constituents likely contribute to the initiation and orchestration of alloantibodies to RBC antigens, identification of key immune factors that initiate alloantibody formation may aid in the development of a therapeutic modality to minimize or prevent this process. To define the immune factors that may be important in driving alloimmunization to an RBC antigen, we determined the specific immune compartment and distinct cells that may initially engage transfused RBCs and facilitate subsequent alloimmunization. Our findings demonstrate that the splenic compartment is essential for formation of anti-KEL antibodies following KEL RBC transfusion. Within the spleen, transfused KEL RBCs are found within the marginal sinus, where they appear to specifically co-localize with marginal zone (MZ) B cells. Consistent with this, removal of MZ B cells completely prevented alloantibody formation following KEL RBC transfusion. While MZ B cells can mediate a variety of key downstream immune pathways, depletion of follicular B cells or CD4 T cells failed to similarly impact the anti-KEL antibody response, suggesting that MZ B cells may play a key role in the development of anti-KEL IgM and IgG following KEL RBC transfusion. These findings highlight a key contributor to KEL RBC-induced antibody formation, wherein MZ B cells facilitate antibody formation following RBC transfusion.